Does Change in Physical Activity During the Initial Phase of the COVID-19 Pandemic Predict Psychological Symptoms in Physically Active Adults? A Six-Month Longitudinal Study - Audun Havnen; Audun Havnen; Linda Ernstsen (Frontiers Media S.A., 2022)
Objectives: The current study aimed to investigate if change in physical activity during the initial phase of the COVID-19 pandemic predicted severity of anxiety and depression symptoms 6 months later in physically active adults.Methods: A total of 855 respondents (32.6% women) completed the Hospital Anxiety and Depression Scale (HADS) at two time points and reported change in physical activity habits in the first 3 months of the COVID-19 lockdown in Norway.Results: Women had higher prevalence rates than men for both anxiety and depression symptoms in the Unchanged, Increased and Decreased physical activity (PA) subgroups. Women and men who reported Increased PA at baseline were associated with increased risk for anxiety symptoms at time 2. Increased PA was associated with higher risk for depression at time 2 for women, but not for men.Conclusion: The results indicate that the COVID-19 pandemic is associated with deterioration in mental health also for physically active adults.